A dynamic model of personality, schooling, and occupational choice. Issue 1 (3rd February 2020) - Todd, Petra E.; Zhang, Weilong
Abstract : This paper develops a dynamic model of schooling and occupational choices that incorporates personality traits, as measured by the "big five" traits. The model is estimated using the HILDA dataset from Australia. Personality traits are found to play an important role in explaining education and occupation choices over the lifecycle. Results show that individuals with a comparative advantage in schooling and white‐collar work have, on average, higher cognitive skills and higher personality trait scores. Allowing personality traits to evolve with age and with schooling proves to be important to capturing the heterogeneity in how people respond to educational policies. The estimated model is used to evaluate two education policies: compulsory senior secondary school and a 50% college tuition subsidy. Both policies increase educational attainment and also affect personality traits.